STRATEGI KOMUNIKASI DINAS PARIWISATA DAN KEBUDAYAAN DALAM MENARIK MINAT WISATAWAN AIR TERJUN AEK MARTUA DI KABUPATEN ROKAN HULU - Yulia Pratiwi; Hevi Susanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Aek Martua Waterfall is a tourist attraction in Rokan Hulu Regency which can be used as a tourist attraction in Riau Province. The purpose of this study is to determine the strategy of selecting communicators, composing messages, selecting media and determining audiences. This study used qualitative research methods . The subjects in this study numbered six people with a purposive technique, namely by selecting informants who were considered to know and could be trusted to become data sources. Data collection techniques consist of observation, interviews and documentation. While the data analysis technique is by reducing data, collecting data, presenting data, drawing conclusions and evaluating using data validity checking techniques, namely the extension of participation and triangulation. The results of this study indicate that the communication strategy carried out by the Tourism and Culture Office of Rokan Hulu Regency in attracting tourists to Aek Martua Waterfall in Rokan Hulu Regency is to determine communicators who have credibility and extensive knowledge about Aek Martua tourist destinations, as for strategies in compiling message is to convey informative messages while in the media selection strategy, the Tourism Office uses social media Instagram, Facebook and Youtube, then in determining targets or audiences, the Tourism and Culture Office does not determine criteria because Aek Martua Waterfall tourism can be visited from all walks of life both young and old. Keyword : communication strategy, tourism, tourist visits